Percepção da qualidade de vida dos moradores da Ilha Mem de Sá, Itaporanga D'Ajuda/SE - Limeira, Célia Maria Cardoso de Rezende (2017)
This study aims to evaluate the perception of changes in the quality of life of the Mem de Sá Island community, Itaporanga D'Ajuda-SE, based on the projects and extension actions of the Federal Institute of Sergipe-IFS, which occurred during the years 2014-2016. These projects and extension actions were carried out by the Superior Course of Management in Tourism / IFS, aiming to contribute to the process of organization of the inhabitants of the Island, as well as to develop proposals of development of the tourist activity in the place, for example Community Based Tourism (TBC), and the Ecotourism Management model, identified as tools for promoting income generation, promoting social and economic equity in a sustainable way. As for the sustainability question, it is evidenced mainly by virtue of the landscape potential of the village, as well as by the forms of management and community practices of social organization around the environmental conditions of the Island itself - its biome. Methodologically, this study is characterized as an exploratory, qualitative and quantitative research, added to the phenomenological method, which allowed presenting a reflection on the relationship established between the IFS and the studied community. Such community that forms the non-probabilistic sample used here, of the 24 (twenty four) residents of the island who participated in the projects and actions mentioned above, and to obtain the data, these were acquired through the use of participant observation, interview application (Semistructured), conversations with local leaders, as well as the utilization of the WHOQOL-bref questionnaire - used to capture the community's perception of their feelings about changes in the quality of life. In this way, through the data analyzed, it was possible to perceive, apprehend and confront the elements obtained through the research instruments with the reality observed in the island, allowing to verify the influences that IFS had on the aesthetics and social dynamics of this village, as well as to signal the main changes in the quality of life of this population, in terms of their "wants and needs", converted into indicators of quality of life built by the perception of the local community.